A landscape‐scale framework to identify refugia from multiple stressors. Issue 1 (26th October 2021) - Rojas, Isabel M.; Jennings, Megan K.; Conlisk, Erin; Syphard, Alexandra D.; Mikesell, Jack; Kinoshita, Alicia M.; West, Krista; Stow, Doug; Storey, Emanuel; De Guzman, Mark E.; Foote, Diane; Warneke, Alexandria; et al.
Abstract: From a conservation perspective, quantifying potential refugial capacity has been predominantly focused on climate refugia, which is critical for maintaining the persistence of species and ecosystems. However, protection from other stressors, such as human‐induced changes in fire and hydrology, that cause habitat loss, degradation, and fragmentation is also necessary to ensure that conservation efforts focused on climate are not undermined by other threats. Thus, conceptual and methodological advances for quantifying potential refugia from multiple anthropogenic stressors are important to support conservation efforts. We devised a new conceptual approach, the domains of refugia, for assessing refugial capacity that identifies areas where exposure to multiple stressors is low. In our framework, patterns of environmental variability (e.g., increased frequency of warm summers), thresholds of resilience, and extent and intensity of stressors are used to identify areas of potential refugia from a suite of ongoing anthropogenic stressors (e.g., changes in fire regime). To demonstrate its utility, we applied the framework to a Southern California landscape. Sites with high refugial capacity (super‐refugia sites) had on average 30% fewer extremely warm summers, 20% fewer fire events, 10% less exposure to altered river channels and riparian areas, and 50% fewer recreational trails than the surrounding landscape. Our results suggest that super‐refugia sites (∼8200 km 2 ) for some natural communities are underrepresented in the existing protected area network, a finding that can inform efforts to expand protected areas. Our case study highlights how considering exposure to multiple stressors can inform planning and practice to conserve biodiversity in a changing world. Abstract : Article impact statement : Identifying refugia from multiple stressors can inform conservation plans that aim to protect biodiversity in a changing world. Abstract : Marco Conceptual a para Identificar Refugios de Múltiples Amenazas a Escala de Paisaje Resumen: Desde la perspectiva de la conservación, la cuantificación de la capacidad potencial de refugio se ha enfocado principalmente en los refugios climáticos, los cuales son críticos para mantener la persistencia de las especies y los ecosistemas. Sin embargo, la protección ante otros factores estresantes, como los cambios inducidos por los humanos en los incendios y la hidrología, que causan la pérdida, degradación y fragmentación del hábitat, también son necesarios para asegurar que los esfuerzos de conservación enfocados en el clima no sean afectados por otras amenazas. Por lo tanto, los avances conceptuales y metodológicos para cuantificar los refugios potenciales ante múltiples factores estresantes causados por el humano son importantes para asegurar que los esfuerzos de conservación logren sus objetivos. Diseñamos una nueva estrategia conceptual, los dominios de los refugios, para evaluar la capacidad de refugio de un paisaje donde la exposición a múltiples factores estresantes es baja. En nuestro marco conceptual usamos los patrones de variabilidad ambiental (p. ej.: incremento en la frecuencia de veranos cálidos), los umbrales de resiliencia y la extensión e intensidad de los factores estresantes para identificar las áreas de refugios potenciales a partir de un conjunto de factores antropogénicos persistentes (p. ej.: cambios en el régimen de incendios). Para demostrar su utilidad, aplicamos el marco conceptual a un paisaje del sur de California. Los sitios con una alta capacidad de refugio (sitios de súper‐refugios) tuvieron en promedio un 30% menos veranos extremadamente cálidos, 20% menos eventos de incendios y 50% menos senderos recreativos que el paisaje circundante. Nuestros resultados sugieren que los sitios de súper‐refugios (∼ 8, 200 km 2 ) para algunas comunidades naturales están subrepresentados en la red existente de áreas protegidas, un resultado que puede orientar los esfuerzos por expandir las áreas protegidas. Nuestro estudio de caso resalta que considerar la exposición a múltiples amenazas puede guiar la planificación y la práctica de la conservación de la biodiversidad en un mundo cambiante. 【摘要】: 从保护的角度来看, 目前对潜在避难能力的量化主要关注的是气候避难所, 它们对于维持物种和生态系统续存至关重要。然而, 为了确保关注气候的保护工作不受其它威胁因素破坏, 还需要考虑针对其它压力因素的保护, 包括人类引起的火灾和水文变化, 因为它们会导致栖息地丧失、退化和破碎化。因此, 在概念和方法上推动量化多种人为压力因素的潜在避难所的研究进展, 对支持保护工作十分重要。本研究设计了一个新的概念性方法 (即避难所领域) 用于评估避难能力, 以识别受多种压力因素影响较小的地区。我们的框架利用环境变异性格局 (如暖夏出现频率增加) 、恢复力阈值, 以及压力因素的范围和强度来识别一系列持续的人为压力因素 (如火灾变化) 影响下的潜在避难所。为了证明该框架的有效性, 我们将其应用于南加州的一处景观之中。结果表明, 与周围景观相比, 具有高避难能力的位点 (超级避难所) 极端暖夏出现的概率平均低 30%, 火灾出现概率平均低 20%, 河道和河岸地区被改变的风险低 10%, 且存在的休闲步道少 50%。我们的结果指出, 一些自然群落的超级避难所 (约 8, 200 平方公里) 在现有的保护区网络中的代表性不足, 这一发现可以指导扩大保护区的工作。我们的案例研究还强调了考虑多种压力因素的暴露情况将如何为规划和实践提供信息, 从而在不断变化的世界中保护生物多样性。 【翻译: 胡怡思; 审校: 聂永刚】